STRATEGI PENGEMBANGAN KOMPETENSI PENYULUH DI KECAMATAN BANDA BARO KABUPATEN ACEH UTARA - Martina, Martina; Zuriani, Zuriani; Zahara, Hafni (LPPM Universitas Malikussaleh - Indonesia, 2022)
The implementation of agricultural extension activities in Banda Baro Subdistrict aims to increase the amount of agricultural production of farmers, add insight or skills of farmers in farming activities and in adding infrastructure for farmer groups, in addition to other general services needed by farmers in order to increase the empowerment of farmers, so that extension workers as field implementers must have good competence so that extension is carried out effectively. In their duties, agricultural instructors in Banda Baro District are not free from perceived obstacles such as the difficulty of holding direct meetings with farmers, the limited number of instructors, the difficulty of accessing transportation to locations and the difficulty of communication networks. The research aims to formulate a strategy for developing the competency of agricultural instructors in Banda Baro District, North Aceh Regency. Data analysis using SWOT Analysis. The research results show that in the SWOT position matrix. The strategy for increasing instructor competency shows that the position matrix is in quadrant I supporting the SO (Growth oriented strategy) strategy, meaning that the competency of agricultural instructors has a very favorable situation. The instructor's competency has strengths and opportunities so that he can take advantage of these opportunities by growing existing strengths.